A comparative evaluation of the shaping ability of four different single-file systems in severely curved mesiobuccal root canals of mandibular first molars: An in vitro study - Vivek Kumar Pathak; Rajnish K Singhal; Anurag Jain; Saurabh Mankeliya; Kaushal Singh; Ashish Sharma (Wolters Kluwer Medknow Publications, 2021)
Aim: The aim of this study was to compare the shaping ability of four different single-file systems in severely curved mesiobuccal root canals in extracted human mandibular first molars. Materials and Methods: Sixty extracted intact human mandibular first molars with at least one curved mesial root were collected and used for the study. The study samples (n = 60) were divided into four experimental groups (n = 15 each): WaveOne (WO) (Group I), WaveOne Gold (WOG) (Group II), OneShape (Group III), and F360 (Group IV). The working length was established. All the study samples were prepared with respective file systems according to manufacturer's instructions. Pre- and postinstrumentation radiographs were taken and images were transferred to AutoCAD 2016 to determine the radius of curvature of each root canal. The canal curvature was assessed as a difference between before and after instrumentation to determine canal straightening. The data obtained were subjected to statistical analysis using SPSS version 20.0. Results: The pre- and postinstrumentation readings were compared using one-sample t-test, and difference was found to be statistically significant (P < 0.05). The mean difference in root curvature was estimated by pre- and postinstrumentation readings. According to mean change in the root curvature, the order determined was Group IV < III < II < I. Intergroup comparison was conducted using ANOVA statistical analysis, and it was found to be statistically significant. Conclusion: WOG and WO reciprocating files showed a marked tendency to straighten the severely curved canals, whereas F360 and OneShape continuous files maintained the original canal curvatures well.